(untitled) (Biological Sciences - PJSIR, 2002)
Various derivatives of heterocyclic compounds are used in chemotherapy (Wilson et al 1972). Some of the derivatives of nitrofuran-2-carboxaldehyde such as Nitrofura ntoin and Ni trofurazone are excellent antibacterical agents